2010
DOI: 10.1007/s11096-010-9440-7
|View full text |Cite
|
Sign up to set email alerts
|

Which factors predict the time spent answering queries to a drug information centre?

Abstract: Objective To develop a model based upon factors able to predict the time spent answering drug-related queries to Norwegian drug information centres (DICs). Setting and method Drug-related queries received at 5 DICs in Norway from March to May 2007 were randomly assigned to 20 employees until each of them had answered a minimum of five queries. The employees reported the number of drugs involved, the type of literature search performed, and whether the queries were considered judgmental or not, using a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 10 publications
1
30
1
5
Order By: Relevance
“…In the present study, they were used to indicate complex questions. In an earlier study, we found that more than 60% of the queries were judgemental and most of the queries were patient-related 8. The sample in that study was much smaller compared with the present results, but the numbers corresponds well.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In the present study, they were used to indicate complex questions. In an earlier study, we found that more than 60% of the queries were judgemental and most of the queries were patient-related 8. The sample in that study was much smaller compared with the present results, but the numbers corresponds well.…”
Section: Discussioncontrasting
confidence: 65%
“…This is illustrated by the finding that the average number of references in the QAPs did not decrease from the first to the second period and advanced search strategies were still used in most cases. We recently performed a prospective study where the extent of literature search was the individual factor best predicting the time spent answering questions in RELIS 8. However, in RELIS, repeated questions are subjected to a new literature search if 3 months have passed since a previous answer was provided, and this was more likely to happen in the period 1995–2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary sources like journals were less frequently used. The reasons might be easiness of the queries to answer by tertiary references, unavailability, or rare availability of primary references and DI pharmacists' level of understanding of such materials [37]. Information from guidelines, Drugdex, leaflet, phone contact, protocols, store man, and monograph was also used to reply queries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of appropriate and credible sources along with critical literature evaluation skills [2] may be more important than exactly what type of source is used. The great workload of some centres may limit their ability to scrutinise the primary literature, as this kind of searching is time consuming [21, 22]. Especially for frequently asked queries where the evidence is comprehensive, e.g.…”
Section: Discussionmentioning
confidence: 99%